Public Libraries: Readers and Books. A Case Study on Services for Minor Readers in Guangdong, China - Song Ling (Библиосфера)
The purpose of this article is to clarify the evolving connotations of “readers” and “books” in public libraries, centers on a thriving segment of library patrons – minor readers. Taking the services for minors in Guangdong China as an example, the study examines and discusses how public libraries can play a proactive role in forging effective connections between readers and books, hence promoting the sustainable development of library services. The author has come to the conclusion that public libraries worldwide must proactively adapt to the ever-evolving environment, cutting-edge technologies, and emerging information needs.